Effectiveness of Risk-Based Business Licensing Supervision in Layer Chicken Farming Business in Buleleng Regency - A. A. Istri Agung Sita Pratiwi; Ni Made Jaya Senastri; I Wayan Rideng (Jurnal Hukum Prasada, 2025)
Law Number 6 of 2023 on Job Creation encourages ease of doing business through Risk-Based Business Licensing. Buleleng Regency is one of the regencies in Bali Province where the agricultural sector is quite developed. In this region, there are several business actors focusing on the laying hen farming business, which is dominated by micro-scale businesses. Micro-scale layer chicken farming in Buleleng Regency is classified as medium to low risk, with licensing consisting of NIB and Standard Certificate in the form of self-declaration. In micro businesses, the NIB has been integrated with environmental approval in the form of an Environmental Management and Monitoring Letter (SPPL). However, the automatic issuance of licenses through OSS without verification raises concerns about the implementation of environmental obligations in the SPPL. Given that Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia affirms that everyone has the right to a good and healthy environment, the fulfillment of environmental commitments is an aspect that cannot be ignored. This research aims to analyze the effectiveness of business licensing supervision in layer chicken farming businesses in Buleleng Regency. Using a juridical-empirical approach, it is found that weak supervision contributes to violations of environmental commitments and potential pollution. Therefore, it is necessary to strengthen the supervision mechanism and increase the legal awareness of business actors to improve the effectiveness of supervision.